2007
DOI: 10.1159/000099597
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fluid Cushion in the Submucosal Layer by Water Jet: Advantage for Endoscopic Mucosal Resection

Abstract: Background/Aim: Numerous new techniques have recently been reported and described for the endoscopic mucosal resection of large superficial lesions of the gastrointestinal tract. We present here for the first time the application of a water jet dissector for mucosa elevation. Materials and Methods: In an ex vivo study, the effectiveness of a water jet dissector (Helix Hydro-Jet®) placed directly on the stomach walls of 8 pigs was examined to create a mucosal elevation. After having determined optimal pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…Following earlier studies performed by Farin [12], Schurr et al [13], and Ehrhardt et al [14], our study group demonstrated the suitability of the water-jet technology for mucosal elevation before EMR in experimental and clinical investigations [15,16]. The focused water-jet, which can be applied using a wide range of therapeutic pressures ranging from 20 to 80 bar, is capable of penetrating the mucosa from different angles and creates a selective accumulation of liquid exclusively in the submucosal lamina.…”
Section: Introductionsupporting
confidence: 59%
“…Following earlier studies performed by Farin [12], Schurr et al [13], and Ehrhardt et al [14], our study group demonstrated the suitability of the water-jet technology for mucosal elevation before EMR in experimental and clinical investigations [15,16]. The focused water-jet, which can be applied using a wide range of therapeutic pressures ranging from 20 to 80 bar, is capable of penetrating the mucosa from different angles and creates a selective accumulation of liquid exclusively in the submucosal lamina.…”
Section: Introductionsupporting
confidence: 59%
“…The water jet technology with a continuous pressure-driven water flow was initially used in liver surgery in the 1980s [13], and, thereafter, in neurosurgery [19], and stomach [20], colon [21], cardiovascular [22] and ophthalmological [23] surgeries. It might be beneficial in that the water jet, as a no-touch technique, is less traumatic to the vascular structures than the directly applied ultrasonic aspirator tip [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has demonstrated a clear technical advantage over the conventional surgical dissection modalities. It allows: i) a selective dissection of fibrous and connectives tissues, preserving blood vessels for delayed ligation; [37][38][39] ii) 44 demonstrated that submucosal injection of a saline solution using WJ provides a selective long-lasting SFC for over 20 min. These results were confirmed by the same team in a study on humans obtaining long-lasting SFC for over 40 min using other solutions such as plasma expanders.…”
Section: Water-jet Technologymentioning
confidence: 99%